There is influence on Self-control from Restrained Eating - Luo, Jing (International Journal of Public Health and Medical Research, 2025)
The purpose of this experiment was to explore the self-control ability of subjects in restrictive diet. The collocation scores of subjects in daily eating were measured by test, and the data were analyzed by SPSS statistical method. Based on reviewing the previous studies, this paper carries out experiments, pointing out that the self-control ability of different types of food eaters can be studied from the perspective of picture stimulation food temptation. Through horizontal comparison, the influence of weight loss psychology on personal control can be proved finally. It is hoped that we can find out the problems and provide reference information for solving the problem of obesity and losing weight.